2002
DOI: 10.1094/pdis.2002.86.6.652
|View full text |Cite
|
Sign up to set email alerts
|

Gaeumannomyces graminisvars.avenae, graminis, andtriticiIdentified Using PCR Amplification of Avenacinase-like Genes

Abstract: Identifying take-all pathogens, Gaeumannomyces graminis varieties avenae (Gga), graminis (Ggg), and tritici (Ggt), is difficult. Rapid identification is important for development of disease thresholds. We developed a single-tube, polymerase chain reaction (PCR) method differentiating among Gga, Ggg, and Ggt. Nucleotide base sequence analyses of avenacinase-like genes from Gga, Ggg, and Ggt isolates provided the basis for designing variety-specific primers. Sequences from Ggg and Ggt were highly related (99% id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…For analysis of R. secalisinfected samples, the primers RS8mod2 (CCAGAG-GACCACAACTCTTGTT) and RS9mod2 (AAGG CGCAATGTGCGTTCAAA) were used to amplify a fragment from the 5.8S RNA gene of R. secalis (Lee et al 2001). For analysis of G. graminis-infected samples, the primers AV3 (TGCTCATGGTGG TTCCTGCG) and Ggt_for1 (GGTCAGGACAAG GACTACCC) were used to amplify a fragment from the Avenacinase-like gene of G. graminis (Rachdawong et al 2002). Each 96-well PCR plate contained the standard curve samples, non-template control and samples to be analyzed in threefold replicates.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…For analysis of R. secalisinfected samples, the primers RS8mod2 (CCAGAG-GACCACAACTCTTGTT) and RS9mod2 (AAGG CGCAATGTGCGTTCAAA) were used to amplify a fragment from the 5.8S RNA gene of R. secalis (Lee et al 2001). For analysis of G. graminis-infected samples, the primers AV3 (TGCTCATGGTGG TTCCTGCG) and Ggt_for1 (GGTCAGGACAAG GACTACCC) were used to amplify a fragment from the Avenacinase-like gene of G. graminis (Rachdawong et al 2002). Each 96-well PCR plate contained the standard curve samples, non-template control and samples to be analyzed in threefold replicates.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Specific PCR assays for identification of Ggt, Ggg and Gga, based on avenacinase and avenacinase‐like gene sequences, have recently been developed (Rachdawong et al ., 2002). Variety‐specific forward PCR primers were used, singly and together, with a common reverse PCR primer to give amplification products of different sizes from DNA of Ggt, Ggg and Gga isolates.…”
Section: Detection and Identification Of G Graminis Varieties By Dnamentioning
confidence: 99%
“…The avenacinase‐minus mutant was no longer pathogenic on oats but was still able to infect wheat. Ggt and some other members of the Gaeumannomyces–Phialophora complex also contain DNA sequences homologous to the avenacinase gene even though they are unable to inactivate avenacin effectively (Osbourn, 1996a; Osbourn et al ., 1994a; Rachdawong et al ., 2002). The role of these avenacinase‐like genes is uncertain but it has been suggested that they might be involved in producing enzymes that detoxify other saponins in hosts other than oats (e.g.…”
Section: Factors Implicated In Pathogenicity and Host Range Determinamentioning
confidence: 99%
“…Recently, G. graminis var. avenae (E.M. Turner) Dennis was described as affecting oat in Chile (Gutiérrez et al, 2007); however, this pathogen also may affect wheat (Rachdawong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%